Perceived organizational customer orientation and frontline employees' innovative behaviors: exploring the role of empowerment and supervisory fairness. Issue 2 (11th June 2020) - Quratulain, Samina; Al-Hawari, Moh'D Ahmad; Bani-Melhem, Shaker
Abstract : Purpose: The purpose of this research is to examine the indirect effect of perceived organizational customer orientation on frontline employees' (FLE) innovative behaviors (via perceived empowerment) as well as the contextual factor of supervisory fairness, which affects the strength of the indirect effect. Drawing on social exchange theory, the authors propose that FLEs' perceived organizational customer orientation positively affects their empowerment and indirectly affects innovative behaviors, and that effect is stronger in a high supervisory fairness condition. Design/methodology/approach: Structural equation modeling of the data collected through a time-lagged survey of 184 employee–supervisor dyads provides support for the hypotheses. From the practitioners' perspective, this study highlights the mechanism through which perceived organizational customer orientation can affect the display of FLEs' innovative behaviors as well as the conditions that strengthen this process. Findings: Perceived organizational customer orientation was positively related to employees' perceived empowerment. Empowerment was positively associated with supervisor-reported innovative behaviors. The indirect effect of perceived organizational customer orientation through employee empowerment on supervisor-reported innovative behaviors was also confirmed. Supervisory fairness significantly moderated the perceived organizational customer orientation and employee empowerment relationship. Finally, the indirect effect of customer orientation on supervisor-reported innovative behaviors through empowerment was significant for both high supervisory fairness and low supervisory fairness; however, the effect was stronger in a high fairness condition. Practical implications: Service managers can benefit from these findings by improving the work environment characteristics. Originality/value: This study makes an important contribution to existing research on perceived organizational customer orientation and FLEs' innovative behaviors as extant research has only examined the direct unmediated effect of customer orientation on innovative behaviors. Moreover, the authors' moderated mediation model presents a new insight into how perceived organizational customer orientation influences FLEs' innovative behaviors and when this effect is more pronounced.